2019
DOI: 10.18502/crcp.v4i2.1706
|View full text |Cite
|
Sign up to set email alerts
|

Management of Pulmonary Embolism and Pericardial Effusion

Abstract: Pulmonary embolism is a serious complication occurring in different cancers. Patients who have cancer may have complications like brain metastasis or pericardial effusion, which may change the therapeutic management of pulmonary embolism. In this article, a patient is presented with lung adenocarcinoma resulting in pericardial effusion. He was admitted with pulmonary embolism and atrial flutter, which made his management difficult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…We performed the literature review and found 11 previously documented cases of pericardial effusion and pulmonary embolism as concomitant cancer complications from 2000 to 2022 [13][14][15][16][17][18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We performed the literature review and found 11 previously documented cases of pericardial effusion and pulmonary embolism as concomitant cancer complications from 2000 to 2022 [13][14][15][16][17][18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Seven patients (64%) received treatment with anticoagulants. Four of seven patients survived (the survival rate is 57%), one died after pericardiocentesis (14%), one died after 3 months (14%), and one outcome is not clear (14%) [14][15][16][18][19][20]23] (Table 1). From those four patients who did not receive treatment with anticoagulants: one of them survived (25%), one died after 6 weeks (25%), and two outcomes are not clear (50%) [13,17,21,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation